2009
DOI: 10.1259/bjr/90100265
|View full text |Cite
|
Sign up to set email alerts
|

Distinction between pyogenic brain abscess and necrotic brain tumour using 3-tesla MR spectroscopy, diffusion and perfusion imaging

Abstract: The purpose of this study is to compare the effectiveness of relative cerebral blood volume, apparent diffusion coefficient and spectroscopic imaging in differentiating between cerebral abscesses and necrotic tumours. In the prospective study, a 3-tesla MR unit was used to perform proton MR spectroscopy, diffusion and perfusion imaging in 20 patients with cerebral abscesses and 26 patients who had solitary brain tumours (14 high-grade gliomas and 12 metastases). We found the mean apparent diffusion coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 26 publications
4
46
0
1
Order By: Relevance
“…3). Three authors reported a significant difference between ADC values of cerebral abscesses and malignant tumours [15, 16, 19]; the other authors did not provide P -values.
Fig. 3Apparent diffusion coefficient (ADC) values of intracranial lesions.
…”
Section: Resultsmentioning
confidence: 99%
“…3). Three authors reported a significant difference between ADC values of cerebral abscesses and malignant tumours [15, 16, 19]; the other authors did not provide P -values.
Fig. 3Apparent diffusion coefficient (ADC) values of intracranial lesions.
…”
Section: Resultsmentioning
confidence: 99%
“…10 Recently, investigators and clinicians have noted an interesting phenomenon in patients with malignant glioma treated with bevacizumab, consisting of lesions with conspicuously low ADC, which persists over long periods of time. [11][12][13] While DWI has been used to characterize tumor burden in glioblastoma 14 and to differentiate necrotic cystic brain tumors such as glioblastomas from abscesses, 15 the clinical significance of these persistent restricted-diffusion lesions arising during bevacizumab treatment in malignant gliomas is less straightforward. While some investigations suggest that these lesions reflect hypercellular and aggressive tumor, 11 other studies suggest that these lesions represent chronic hypoxia and atypical gelatinous necrotic tissue.…”
mentioning
confidence: 99%
“…However small abscess and non-pyogenic abscesses, such as toxoplasmosis, can display increased diffusion (51). A few studies have demonstrated a significantly lower rCBV ratio (< 0.95) in the abscess wall than in tumor wall (Figure 2) (52,53). One study demonstrated that K trans and v e could also be helpful for this distinction (54).…”
Section: Brain Tumormentioning
confidence: 99%